Reliability-based Design Optimization for the Capacitor of Traction Converter with No Secondary Resonant Circuit - LIU Da; ZENG Yang; SHU Yi; LIN Zhenjun; LUO Rongzheng (Kongzhi Yu Xinxi Jishu)
In order to ensure the robust and reliable operation of capacitor, this paper describes the basic design principle of the support capacitor of traction converter with no secondary resonant circuit in Fuxing EMU and constructs a corresponding simulation model. Based on this model, a reliability-based design optimization (RBDO) for the capacitor is proposed. It takes the uncertainty of capacitance caused by manufacturing and mesasurement errors and the fluctuation of the network voltage into account. In addition, the ripple wave of the intermediate DC circuit voltage is defined as constraint. Compared with the traditional optimization method, this method is more robust. Based on the optimized capacitor, a traction converter with no secondary resonant circuit is accomplished. Test results show that the DC circuit voltage of the converter fluctuates within ±5% ,the volume of the converter is reduced by 28.4% and its weight is reduced by 28%. Effectiveness of the proposed method and the advantages of the traction converter with no secondary resonant circuit in terms of volume and weight are verified.